2019
DOI: 10.1111/tbed.13341
|View full text |Cite
|
Sign up to set email alerts
|

Similar frequency of Porcine circovirus 3 (PCV‐3) detection in serum samples of pigs affected by digestive or respiratory disorders and age‐matched clinically healthy pigs

Abstract: Porcine circovirus 3 (PCV‐3) has been identified in pigs affected by different disease conditions, although its pathogenicity remains unclear. The objective of the present study was to assess the frequency of PCV‐3 infection in serum samples from animals suffering from post‐weaning respiratory or digestive disorders as well as in healthy animals. A total of 315 swine serum samples were analysed for PCV‐3 DNA detection by conventional PCR; positive samples were further assayed with a quantitative PCR and partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 25 publications
1
28
2
Order By: Relevance
“…Particularly, 73 individual swine serum samples were obtained from 4-week-to 4-month-old pigs clinically diagnosed with respiratory signs (including interstitial/necrotizing pneumonia and pleuritis) (n = 30), and animals displaying enteric signs like atrophy-fusion of villi and catarrhal enteritis (n = 30) as well as healthy animals (n = 13). These samples were part of a set processed in a previously published article (Saporiti et al, 2020) [13]. Fifteen fetal tissue samples (eight from brains and seven from lungs) were also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, 73 individual swine serum samples were obtained from 4-week-to 4-month-old pigs clinically diagnosed with respiratory signs (including interstitial/necrotizing pneumonia and pleuritis) (n = 30), and animals displaying enteric signs like atrophy-fusion of villi and catarrhal enteritis (n = 30) as well as healthy animals (n = 13). These samples were part of a set processed in a previously published article (Saporiti et al, 2020) [13]. Fifteen fetal tissue samples (eight from brains and seven from lungs) were also analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…Also, higher PCV3 infection rates have been reported in animals with digestive and respiratory diseases (Qi et al, ). However, not all studies support the putative role of PCV3 as a major threat to swine health (Franzo et al, ; Kim et al, ; Saporiti et al, ). Prevalence data presented here do not support the positive association of PCV3 infection with enteric‐disease‐causing or respiratory‐disease‐causing viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies, PCV-3 has been identified in different mammalian wild species such as wild boars and wild ruminants [12][13][14][15]. Interestingly, the frequency of the detection of viral DNA in wild boars originating from different European countries can be even higher (ranging from 23% and 50%) than the one reported in domestic pigs (from 6% to 32%) [2,[7][8][12][13][14][15][16][17]. This high prevalence in wild boars was predictable, since wild boars and domestic pigs pertain to the same species, and most of the infectious agents infecting the domestic pigs are also circulating in the wild boars [18,19].…”
Section: Discussionmentioning
confidence: 96%
“…DNA extraction was performed from 200 µL of serum sample by using MagMAX™ Pathogen RNA/DNA kit (Applied Biosystem®). The presence of PCV-3 DNA was assessed by means of a conventional PCR assay detecting a 418-bp fragment of replication gene as previously described (Saporiti et al, 2019) [7]. Briefly, the 25 µL reaction volume contained 2.5 µL of extracted DNA, 12.5 µL of Go Taq®G2 Green Master Mix (Promega), 1 µL of each primer (10 µM), and 8 µL of sterile water.…”
Section: Dna Extraction and Pcv-3 Molecular Diagnosismentioning
confidence: 99%
See 1 more Smart Citation